THE EFFECTIVENESS OF THE PROJECT-BASED LEARNING MODEL IN ENHANCING THE LEGAL AWARENESS OF JUNIOR HIGH SCHOOL STUDENTS IN THE CIVICS (PPKN) SUBJECT - Sopian; Hermansyah; Arik Darojat; Angga Ramdani (Journal Civics And Social Studies, 2026)
The rapid growth of social media presents both challenges and opportunities for developing university students' civic competencies, particularly among Civic Education (PPKn) students as future educators. This article aims to analyze the relationship between digital literacy and digital citizenship among PPKn students in the context of social media use through a systematic literature review. The method employed is a library research design, tracing relevant national and international journal articles through online academic databases, followed by reduction, synthesis, and mapping of fifteen key sources. The findings indicate that digital literacy serves as a foundation for digital citizenship, encompassing ethical, legal, security, online political participation, and social responsibility dimensions in digital spaces. Social media was found to have a dual influence: it can strengthen nationalism and civic participation when used wisely, yet may also trigger deviant behaviors such as cyberbullying when not balanced with adequate digital literacy. Civic Education instruction in higher education needs to explicitly integrate digital literacy reinforcement to prepare students to become intelligent and responsible digital citizens.